Automated food and beverage trolley - Noor Nashriyah Binte Jalil (Nanyang Technological University, 2022)
With the existence of Covid-19, even with loose government restrictions, one can still get infected by the virus due to the consistent discovery of a variant. The intention of this project is to reduce the interaction between an infected individual with a non-infected one. Even though there are Automated Food and Beverage trolleys available in the market, those are expensive and high-cost maintenance. It is also driverless. The aim of this project is to promote social distancing, zero to low cost of maintenance, and encourage students to be exposed to these skills to prepare them for the industry world.